Pathology of acute infectious bursal disease in chickens induced experimentally with a very virulent virus isolate - ISLAMI, M R; CHOWDHURY, E H; DAS, P M; DEWAN, M L (The Indian Journal of Animal Sciences, 2013)
Pathology of acute infectious bursal disease (IBD) was studied in 5-week old layer chicks after experimental oral infection with a very virulent (vv) isolate (BD-6) ofinfectious bursal disease virus (IBDV). The infection resulted in 100% morbidity and mortality. The incubation period was 3 to 4 days. Extreme depression, anorexia and white diarrhoea were the main clinical manifestations. On day 4 or 5 post infection (pi) i.e., within 24 to 48 hr of the onset of illness, 60% birds died while others became progressively weak, emaciated and dehydrated before death with coma between day 7 and 10p i. Pathological changes varied with the course of the disease. Acute death’s were invariably associated with oedematous swelling of the bursa of fabricius, and thymus and haemorrhages in the proventriculus, intestine and caecal tonsils. These lesions were, however, absent in the birds which died on day 7 p i or later, but the bursa and thymus were atrophied. Severe lymphoid depletion, necrosis and haemorrhages in the bursa thymus, spleen and caecal tonsils were the major microscopic lesions.